Habitar no novo céu e na nova terra: uma leitura narrativa de Ap 21,1-8 - Patuzzo, Izabel (2023)
The present study consists of an Exegetical-theological commentary on the perícope of Rev 21:1-8, which prioritizes a synchronic analysis under the perspective of a narrative Reading of the text. The apocalyptic literary genre adopted by the author of the Apocalypse is the result of these minority groups expressing their worldview through Symbolic literature. The following three chapter respectively address the syntax, the theological semantics, and narrative elements of the text. The adopted hermeneutical-theological approach is one in which the author of Revelation points to the events of his time, using Symbolic language to exhort the Christian Communities of Asia Minor to resist the cultural-religious and socio-political imposition that threatens their Christian identity. The narrative reading of the pericope Rev 21:1-8 allowed for an analysis of the plot of the Book of Revelation and the theological significance of this text within the literary context of the narrative woven by the author throughout the work. The setting is one of the central elements of a narrative text. The opening scene of the Book of Revelation, in continuity with the New Testament writings, places Jesus Christ as the main character of this account. He came to save humanity from its sins with His blood. In the vision of the new heaven and the new earth, symbolized by the celestial city of Jerusalem, John’s narrative reaches its climax, for after removing evil from the earth, God and the Lamb establish their dwelling in the holy city, where all listeners and readers are invited to contemplate this new reality, taking an active part in this grand narrative, becoming co-inhabitants of the holy city, and heirs of God’s promise to the victors who resisted the deceptive and idolatrous proposals propagated by the imperial power of the beast